2018
DOI: 10.3389/fmicb.2018.00906
|View full text |Cite
|
Sign up to set email alerts
|

Macrophage Migration Inhibitory Factor (MIF) Prevents Maternal Death, but Contributes to Poor Fetal Outcome During Congenital Toxoplasmosis

Abstract: Migration inhibitory factor (MIF) is a pro-inflammatory cytokine that plays important roles in physiology, pathology, immunology and parasitology, including the control of infection by protozoa parasites such as Toxoplasma gondii. As the MIF function in congenital toxoplasmosis is not fully elucidated yet, the present study brings new insights for T. gondii infection in the absence of MIF based on pregnant C57BL/6MIF-/- mouse models. Pregnant C57BL/6MIF-/- and C57BL/6WT mice were infected with 05 cysts of T. g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 61 publications
0
12
0
1
Order By: Relevance
“…Many studies demonstrated the important protective role of IFN-γ, nitrite (Gazzinelli et al, 1994; Lang et al, 2007; Kemp et al, 2013; Koblansky et al, 2013; Behnke et al, 2017; Abreu-Cabral et al, 2018), IL-17A (Kelly et al, 2005), MIF (Ferro et al, 2008; Flores et al, 2008; Terrazas et al, 2010; Gomes et al, 2011, 2018; Barbosa et al, 2014), TNF and IL-6 (Castro et al, 2013; Barbosa et al, 2014, 2015) during infection by T. gondii . Our recent studies showed that IL-6, TNF and MIF are the most important cytokines involved in the immune response to T. gondii in human trophoblast cells, human explants from third trimester and murine maternal-fetal interface, allowing a significant reduction in the vertical transmission of the parasite (Barbosa et al, 2015; Silva et al, 2017; Gomes et al, 2018). Oliveira et al (2010) observed higher IFN-γ and IL-2 concentrations in serum of rats infected with T. cruzi and treated with meloxicam.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many studies demonstrated the important protective role of IFN-γ, nitrite (Gazzinelli et al, 1994; Lang et al, 2007; Kemp et al, 2013; Koblansky et al, 2013; Behnke et al, 2017; Abreu-Cabral et al, 2018), IL-17A (Kelly et al, 2005), MIF (Ferro et al, 2008; Flores et al, 2008; Terrazas et al, 2010; Gomes et al, 2011, 2018; Barbosa et al, 2014), TNF and IL-6 (Castro et al, 2013; Barbosa et al, 2014, 2015) during infection by T. gondii . Our recent studies showed that IL-6, TNF and MIF are the most important cytokines involved in the immune response to T. gondii in human trophoblast cells, human explants from third trimester and murine maternal-fetal interface, allowing a significant reduction in the vertical transmission of the parasite (Barbosa et al, 2015; Silva et al, 2017; Gomes et al, 2018). Oliveira et al (2010) observed higher IFN-γ and IL-2 concentrations in serum of rats infected with T. cruzi and treated with meloxicam.…”
Section: Discussionmentioning
confidence: 99%
“…During infection, cells from innate immunity, such as macrophages, neutrophils, and dendritic cells recognize the parasite by pathogen-associated molecular patterns (Hou et al, 2011; Koblansky et al, 2013; Gorfu et al, 2014) and produce high levels of pro-inflammatory cytokines, such as interleukin (IL)-12, which activates CD4 + T lymphocytes to produce interferon (IFN)-γ, the major cytokine involved in control of T. gondii (Gazzinelli et al, 1994; Kemp et al, 2013; Koblansky et al, 2013; Behnke et al, 2017). In parallel to IFN-γ, other pro-inflammatory cytokines, such as IL-6, tumoral necrosis factor (TNF), IL-17A, IL-2 and macrophage migration inhibitory factor (MIF) also participate significantly in the immunity against T. gondii (Kelly et al, 2005; Castro et al, 2013; Barbosa et al, 2014, 2015; Gomes et al, 2018). Our previous studies demonstrated that human trophoblast cells controlled T. gondii intracellular proliferation in a MIF-dose-dependent manner, since only high concentrations of recombinant MIF (rMIF) were able to reduce the parasite growth.…”
Section: Introductionmentioning
confidence: 99%
“…The pathophysiology of congenital toxoplasmosis is complex, since it is not only a consequence of foetal infection during pregnancy, but it is also due to the inflammatory immune response to infection during pregnancy . Furthermore, elements of the immune response that are normally associated with a protective immune response to T gondii infection in nonpregnant mice contribute to the pathology associated with congenital infection . In addition, normal pregnancy is dependent on a series of sequential alterations in the maternal immune system, which facilitate implantation, decidualization and prevent rejection of the semiallogeneic foetus .…”
Section: Introductionmentioning
confidence: 99%
“…MIF was found to sustain macrophage survival and proinflammatory function by suppressing activation-induced, p53-dependent apoptosis (Mitchell et al, 2002; Calandra and Roger, 2003; Larson and Horak, 2006; Hertelendy et al, 2018). The cytokines affected by MIF are involved in the pathogenesis of infectious and non-infectious inflammatory diseases (de Oliveira Gomes et al, 2011; Gomes et al, 2018). In a previous study, this conserved protein homolog has been found in different phyla, including many parasitic organisms, and it was capable of facilitating the host immune responses during infection (Zang et al, 2002; Flores et al, 2008; Vermeire et al, 2008; Sommerville et al, 2013; Sparkes et al, 2017).…”
Section: Introductionmentioning
confidence: 99%